What a difference a (birth) month makes: The relative age effect and fund manager performance - Bai, John (Jianqiu); Ma, Linlin; Mullally, Kevin A.; Solomon, David H. (Journal of Financial Economics, 2019)
Many US states have a single cutoff date for school entry, meaning that some children are older than others when they begin kindergarten. We show that this variation in birth months is associated with differences in adult labor market outcomes in the mutual fund industry. Relatively older managers (i.e., those born just after the cutoff) make better stock selections, and their funds outperform their younger peers’ funds by 0.48% per annum. This difference is linked to increased confidence. Survey respondents judge relatively older managers as appearing more confident in photographs, and these managers display more confident behavior: making larger bets, window dressing their holdings less, and securing more fund flows conditional on performance.